The concept of Shiringoma among the Manyika people of Mutasa: navigating the misty horizon between reality and gullibility - Mwandayi, Canisius (University of Kwazulu-Natal, 2022)
The study is a phenomenological navigation of the indeterminate but much talked about concept of Shiringoma among the Manyika people. The paper begins by defining who the Manyika are and then moves on to look at the practice of kuromba ‘acquisition of special powers’ at Shiringoma done by some of the Manyika people. While an outsider may easily dismiss, for example, the idea of a dead person restarting a new existence somewhere as a hoax or something gullible, there are some who really believe it is possible. Kuromba is such a complex phenomenon which makes it difficult, if not almost impossible, to tell realistic appearances from those which are not unless one wasc schooled into the art of performing it or once saw it really happen in one’s life experience. Pieces of data were collected through interviews and especially through snowballing, as the practices at Shiringoma were largely secretive. This paper argues that although kuromba appears unrealistic to the ordinary Zimbabwean, there is evidence that there are some Manyika people who have been initiated into the cult. Therefore, stories about the practice are not products of people who are gullible enough to believe in superstition.